Natural geometrical variations of Italian Phyllostachys edulis bamboo culms for construction purposes - Henrieke Fritz; Matthias Kraus (Advances in Bamboo Science)
Amid the increasing scarcity of raw materials, utilizing bamboo as a renewable building material offers significant environmental and economic benefits for the European construction sector. However, in Europe, the use of bamboo for construction remains limited due to a lack of studies on geometrical and material characteristics of European-cultivated bamboo species. Although bamboo is not typically grown in Europe, the number of bamboo plantations is steadily increasing in countries like Spain, France and Italy. Bamboos growing in temperate climates, however, are exposed to different environmental conditions during growth compared to bamboos from subtropical and tropical climates, such as those in China or Vietnam. As bamboo’s geometric properties are strongly influenced by the environmental conditions during growth, it is essential to investigate how bamboo culms of the same species grown in Europe compare to those from other regions. The present article reports findings on the geometry and geometric imperfections of 90 four-meter Italian bamboo culms. First, the Italian Phyllostachys edulis bamboo culms examined in this study are briefly introduced. Following, geometric imperfections of bamboo culms are defined, and the geometry measurement concept is presented. Subsequently, variations in internode lengths, diameters, wall thicknesses, ovalities, stem tapers and pre-deflections are described and analyzed. Finally, the findings from the Italian culms are compared with those from Asian Phyllostachys edulis. In summary, this article enhances the understanding of the geometric properties of bamboo grown in Europe, thereby advancing the use of cultivated bamboo culms in Europe and improving the overall understanding of bamboo characteristics across different climatic zones.